Description Of The Enzyme Gamma Glutamyl Transferase In The Patient Hepatitis - Amani, Diafa; Kristinawati, Erna; Jiwantoro, Yudha Anggit (Poltekkes Kemenkes Mataram, 2024)
Hepatitis caused by the hepatitis virus is still an endemic disease in Indonesia. Most hepatitis viruses are caused by infection with hepatitis viruses A,B,C,D,E. The large number of hepatitis sufferers requires liver function test, one of which is Gamma Glutamyl Transferase (GGT). Objective: This research aims to find out what the gamma glutamyl transferase enzyme looks like in hepatitis sufferers. This research was carried out at the Mataram City Regional Hospital from November to December 2023. The sampling method was carried out using a simple random sampling technique with a total of 25 samples. Result: Examination of Gamma Glutamyl Transferase levels was obtained from 25 patients suffering from hepatitis who tested positive using the enzymatic colometry method. It was found that GGT levels were increased in 5 patients (20%) with an average increase in GGT levels of 185.2 U/L and the average -average normal GGT level is 22.65 U/L. Conclusions: There was an increase in Gamma Glutamyl Transferase levels in 5 patients (20%).